Infant feeding knowledge and practice vary by maternal HIV status: a nested cohort study in rural South Africa - Yapa, H. Manisha; Drayne, Róisín; Klein, Nigel; De Neve, Jan-Walter; Petoumenos, Kathy; Jiamsakul, Awachana; Herbst, Carina; Pillay, Deenan; Post, Frank A.; Bärnighausen, Till (International breastfeeding journal, 2020)
We investigate whether correct infant feeding knowledge and practice differ by maternal HIV status in an era of evolving clinical guidelines in rural South Africa.